Healing and Antisecretory Effects of Aqueous Extract of Eremomastax speciosa (Acanthaceae) on Unhealed Gastric Ulcers. (19th October 2017) - Amang, A. P.; Mezui, C.; Siwe, G. T.; Emakoua, J.; Mbah, G.; Nkwengoua, E. Z.; Enow-Orock, G. E.; Tan, P. V.
Abstract : Objective . This work investigated the healing and antisecretory effects of the aqueous extract of Eremomastax speciosa on "unhealed gastric ulcers" associated with gastric acid hypersecretion. Materials and Methods . "Unhealed gastric ulcers" were induced using indomethacin following the establishment of acetic-acid-induced chronic gastric ulcers. The extract (200 and 400 mg/kg, per os) was administered concomitantly with indomethacin (1 mg/kg, subcutaneously). The effects of the extract on both basal and histamine-stimulated gastric acid secretion were determined. Mucus secretion and oxidative stress parameters were measured, and histological assessment of ulcer healing was carried out. Results . The extract significantly promoted the healing process in rats subjected to "unhealed gastric ulcers" (82.4–88.5% healing rates). Treatment with the extract significantly reduced the basal (25.95–49.51% reduction rates) and histamine-stimulated (24.25–47.41%) acid secretions. The healing effect of the extract was associated with a significant (p < 0.05 ) increase of mucus secretion and concentrations of antioxidant enzymes compared with the controls. The extract at the highest dose showed normalization of the mucosa, without glandular destruction and with the disappearance of fibrosis and lymphocyte infiltration. Conclusion . The abilities of the extract to increase mucus secretion, to reinforce antioxidant status, and to inhibit acid secretion would be some of the mechanisms by which this extract would accelerate the healing process in "unhealed gastric ulcers."